(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2024)
This study aims to analyse the impact of PR Campaigns on consumer attitudes and purchasing decisions in Saudi Arabia, along with assessing the significance of PR campaigns in businesses, evaluating various ways PR campaigns affect buying decisions and analysing the impact of PR Campaigns on consumer attitudes and purchasing decisions in Saudi Arabia. To attain the objectives of this study, the study employs a primary quantitative method. The data was collected through a closed-ended survey questionnaire and was analysed through SPSS. The results of the study show that PR campaigns have a huge influence on Saudi consumers’ perceptions and buying behaviour. The majority of the participants said they were more likely to buy products after interacting with a PR campaign. This suggests that PR is very useful in influencing the consumer’s actions. To optimise this influence, it is advised that companies improve the message clarity of their campaigns so that these connect with target consumers. Moreover, the integration of the campaign narratives into the commonly held consumer values and the use of more interactive methods of engagement would also go a long way in enhancing the overall brand trust, thus leading to the formation of more long-term consumers’ commitment in such a competitive market.